EFEKTIFITAS MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR GEOGRAFI SISWA KELAS X SMA NEGERI 7 KOTA TERNATE - Sukarni Hi Kadir (Jurnal Geocivic, 2018)
In the process of teaching and learning in succeeds when students are able to understand and master the subjects taught. This study aims to determine student learning outcomes before and after using the learning model of Discovery Learning. The population in this study is all students of class X. Sampling is done using purposive sampling technique with the subject of the class. Methods of data collection research conducted using tests that include pretest and posttest.Teknik data analysis used to test the hypothesis is t test (independent sample t-test) dengantarafsignifikansi5 percent. The results of this study note that the initial ability of students, which is shown by having an average of 51.50 for the experimental class and 50.58 for the control class from the pretest and after the two classes were given different treatment had an average increase was 70.83 for experimental class and 62,25 for control class from result of posttest. From the t-test the average difference with the significant level of 0.05 is calculated> ttable, then Ho is rejected, it means that the average of student learning result using discovery learning learning model is better than the average of learning result that use conventional learning model. This means the use of discovery leraning learning model is more effective in order to improve student learning outcomes.